Response to first line chemotherapy regimen is associated with efficacy of nivolumab in non-small-cell lung cancer. (2nd September 2017) - Kaderbhai, Courèche-Guillaume; Richard, Corentin; Fumet, Jean David; Aarnink, Anne; Ortiz-Cuaran, Sandra; Pérol, Maurice; Foucher, Pascal; Coudert, Bruno; Favier, Laure; Lagrange, Aurélie; Limagne, Emeric; Boidot, Romain; et al.
ABSTRACT: Nivolumab, an anti PD-1 checkpoint inhibitor has demonstrated efficacy in metastatic non-small-cell lung cancer (NSCLC) patients after failure to standard chemotherapy. Standard chemotherapy agents could promote antitumor immune response. We thus examined whether the response to first line chemotherapy could impact on nivolumab benefit. One hundred and 15 patients with NSCLC were included in this retrospective study from 4 different French centers. Forty-three squamous cell carcinomas (SCC), and 72 non-SCC received nivolumab between 2015 and 2016 (3 mg/kg IV Q2W). Response to first-line chemotherapy and to nivolumab was retrospectively assessed on CT-scan by central review. The association between RECIST response to first-line chemotherapy and nivolumab efficacy were determined using Fisher's exact test and Cox proportional hazard model. Respectively 46 (40%), 44 (38%) and 25 (22%) patients experienced partial response (PR), stable disease (SD), or progressive disease (PD) in response to first-line platinum- based chemotherapy. Twenty 5 (21%), 34 (30%), 56 (49%) respectively experienced PR, SD and PD in response to nivolumab. 60% (54/90) of patients who experienced clinical benefit (PR + SD) after first-line chemotherapy also had clinical benefit after nivolumab, while only 20% (5/25) of patients with initial PD subsequently experienced clinical benefit with nivolumab (Fisher's exact test, P = 0.001). The type of first-line doublet chemotherapy did not influence the response rate to nivolumab. Univariate and multivariate analyses showed that patients with clinical benefit from first-line chemotherapy had higher second-line PFS ( P = 0.003) (median PFS on nivolumab of 5, 3.3 and 1.9 months for patients with PR, SD and PD in response to first-line therapy, respectively). Similar results were obtained for OS. Thus this study suggests that the efficacy of first-line chemotherapy may be a valuable surrogate marker of the benefit of nivolumab in terms of PFS and OS.